I’m not Alone: A Phenomenological Study of Psychological Help Sources in Suicide Crisis - F A Nurdiyanto; Subandi Subandi (Faculty of Psychology, Universitas Gadjah Mada, 2021)
This research was conducted to explore the experiences of suicide survivors in seeking psychological help for their crisis. A descriptive phenomenological study was chosen to get the dynamics of mental health help-seeking. Semi-structured interviews were conducted with youth participants who had previously experienced a suicide crisis. Seven participants (5 women; mean age 26 years-old) were involved voluntarily through the snowball technique recruitment. Descriptive phenomenological analysis was applied to get the synthesis and meaning of experiences in psychological help-seeking. This study found psychological help sources: self-help, close relationships, socio-cultural, and institutional. This article highlighted that social relations played a crucial role in the success of seeking help. Suicide prevention should be carried out by campaigning for self-disclosure to seeking help by utilizing various available psychological help sources.